La mujer y la metáfora animal. Una selección crítica de poesía irlandesa contemporánea - Estévez-Saá, Margarita; Manuela Palacios-González; Noemí Pereira-Ares (Estudios Irlandeses, 2020)
In these times of growing ecological awareness, one feels impelled to reflect upon the ways in which contemporary Irish poetry is conceiving and shaping the relationship between human and non-human animal life. Furthermore, social debates about animals’ rights run parallel to inquiries into interconnected forms of oppression and exploitation, as is the case with the discrimination of women around the world (Velasco Sesma 2017). Feminist thought has focused on two ‒ not necessarily incompatible ‒, strategies: one resulting from the urgency to denounce the patriarchal animalization of women ‒ their bodies and their social roles ‒ (Adams 1990), and the other aiming to question anthropocentric, speciesist ideologies that privilege human interests over those of animals (Braidotti 2017).